The Fight against Examination Malpractice: The Way Forward - Abraham Gyamfi; Abraham Yeboah; Patience Langee; Isaac Aboagye Adu; Kingsley Kwasi Erzoah; Eric Atta Quianoo Jnr; Prosper Anthony Mensah; Kennedy Nyeseh Ofori; Grace Aba Mensah; LydiaBoateng Berko; Peter Anolf; Francis Kyei-Badu (Archives of Current Research International, 2022)
Examination malpractice is an unwholesome practice encapsulating different types of malicious means adopted by unserious students to cheat during examinations in order to score high marks and pass the examinations. The incidence of examination malpractice has become so endemic that the penalty hitherto melted out to its perpetrators is almost having no statistically significant effects on them. There is an astronomical increase in the number of people and institutions involved in this social malaise. The public has not thought of the effects and the repercussions of their endorsement of examination malpractice. This paper therefore addresses the prevalence of examinations malpractice, the forms and agents involved in examination malpractice. The paper also highlights the effects of examination malpractice on the economy.